Role of a novel mouse mutant of the Galnt2tm1Lat/tm1Lat gene in otitis media - Ma, Weijun; Li, Heng; Hu, Juan; Gao, Ying; Lv, Hui; Zhang, Xiaotong; Zhang, Qing; Xu, Min; Cheng, Ying (Frontiers in Neurology, 2023)
Genetic susceptibility is one of the most important causes of otitis media (OM). Mutant Galnt2 homozygote (Galnt2tm1Lat/tm1Lat) mimics human otitis media in comparable pathology and causes hearing loss. Otitis media is characterized by effusion and dysregulated mucosa proliferation and capillary expansion in the middle ear cavity, which is associated with hearing loss. The mucociliary dysfunction could be seen in the middle ear cavity (MEC) in a patient harboring the disease that develops in severity with age by a scanning electron microscope. Tumor necrosis factor alpha (TNF-α), transforming growth factor-beta 1 (TGF-β1), Muc5ac, and Muc5b upregulate the expression in the middle ear, which correlates with inflammation, craniofacial development, and mucin secretion. The mouse model with a mutation in the Galnt2 (Galnt2tm1Lat/tm1Lat) was explored in this study as a novel model of human otitis media.